2007
DOI: 10.1213/01.ane.0000258039.79028.7c
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Analysis of Costs Associated with Development of a Cell Salvage Program

Abstract: This analysis suggests that cell salvage can be significantly less expensive than allogeneic blood. The cost of cell salvage in other institutions will vary depending upon case volume, expected levels of blood loss per case, and initial investment costs. A step-by-step formula is provided to assist in the evaluation of a cell salvage service in hospitals of various sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 21 publications
2
49
0
Order By: Relevance
“…As for salvaged blood, two studies have suggested that the volume of ICS cases has direct impact on its cost. (16,17) In a cost analysis study of a cell salvage service that was based on an annual case load of 2,500, (16) a unit of autologous red cells processed by cell salvage cost USD 89.46, while allogeneic red cells cost USD 200. With high case volume, manpower and equipment costs are distributed over a larger patient-consumer population, which then reduces the cost for individuals.…”
Section: Discussionmentioning
confidence: 99%
“…As for salvaged blood, two studies have suggested that the volume of ICS cases has direct impact on its cost. (16,17) In a cost analysis study of a cell salvage service that was based on an annual case load of 2,500, (16) a unit of autologous red cells processed by cell salvage cost USD 89.46, while allogeneic red cells cost USD 200. With high case volume, manpower and equipment costs are distributed over a larger patient-consumer population, which then reduces the cost for individuals.…”
Section: Discussionmentioning
confidence: 99%
“…When enough blood is collected, the necessary items are opened and set up, thus reducing the cost of cell salvage by two-thirds when the collection volume is low and no blood is processed. 17 Ultimately, despite budgetary constraints and hearty debates on cost-effectiveness, it is important to remember that intraoperative blood salvage is not provided to patients to salvage money but to salvage their RBCs 21 and optimize clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…17 Future studies should include all of the associated cost factors involved in the execution of an AAA or AFB surgical repair when using the cell saver device.…”
Section: Limitationsmentioning
confidence: 99%
“…[4][5][6]8,[33][34][35][36] Additionally, we assumed that the operating room time was equivalent with and without the use of intraoperative cell salvage because the machine is setup and run by a separate team of perfusionists 3,5,6 and that the cost per case of intraoperative cell salvage is the same regardless of the need for transfusion or the number of autologous units transfused. 37 The cost per case is taken from data that assume an annual use of intraoperative cell salvage of 2,500 cases. However, the cost per case of intraoperative cell salvage increases if it is used less frequently; therefore, we accounted for use at smaller (and larger) institutions in the sensitivity analysis.…”
Section: Methodsmentioning
confidence: 99%